Al-Amidi's Critical Views and the Reproduction of Meaning in Abu Tammam's Arabic Poetry - Ihab Majeed; Marwah Abdullah; Rabah Hamid; Othman Jaalout (Ijaz Arabi Journal of Arabic Learning, 2026)
The study aims at shedding light on the role of the reader and interpretation in reproducing literary texts. Also, it aims at analyzing Al-Amidi's critical position on Abu Tammam's poetry, and exploring the foundations he relied on in his comparison between him and Al-Buhturi by revealing the mechanisms of interpretation used by Al-Amidi, and the extent of his success in absorbing the specificity of Abu Tammam's poetry. The study aims also at showing the multiplicity of readings and interpretations of Abu Tammam's Spring has been undergone throughout the history of Arabic criticism. The study relies on the critical, analytical and interpretive approach. The sample of the study has endured several aspects of deliberate change to obscure the features of the poetic identity produced by a critic who possesses the depth of vision that qualifies him to lead the march of modernization in poetic performance in an era in which the dominance of heritage prevailed widely, covering the possibilities of transcendence and development in performance. Results have revealed that Al-Amidi’s method continued to present data that do not enrich the text nor enhancing the effective movement, which made the text static and unable to be looked at the text as a renewed movement, as this text stopped at a state of stagnation and inactivity. While, Abu Tammam’s creativity moving from a state of static description to continuous discovery and experimentation of the possibilities of linguistic formation and investing its energies in expression, he works to reproduce the poetic text according to a precise method that goes beyond the familiar and generalities to the circle of continuous discovery.